PENGEMBANGAN MODEL COOPERATIVE LEARNING TIPE JIGSAW BERBASIS MEDIA CARD SORT PADA PENDIDIKAN KEWARGANEGARAAN DI SMA - Adam, Fransisco (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThis research is development of cooperative model of jigsaw type based on media card sort with stages (1) data collection, (2) planning, (3) product development, (4) validation and product trial. The purpose of this research is to develop cooperative learning model of jigsaw type based on card sorting media for learning acquisition on Civic Education. The subjects of the study were students of grade XA SMA Negeri 2 Pontianak amounting to 36 people as a sample. Procedure development using Borg & Gall, with experimental methods. Data collection using instrument (1) expert validation questionnaire, (2) observation, and (3) test result learning. Data were analyzed by quantitative and qualitative analysis. The result of data analysis to learning result before action is known 27.77% result of student learning complete, and 72.21% result of student learning unfinished and after action, known 86.11% result of student learning complete, and 13.88% not complete. This means that an increase in student learning outcomes after the action of cooperative learning type of jigsaw based media card sort on the material Wawasan Nusantara.Â Keywords: Cooperative Learning Type Jigsaw, Media Card Sort.Â